Epidemiological profile of patients subjected to appendectomy in a reference hospital in Vitória, ES (Brazilian Journal of Health Research, 2023)
Introduction: Acute appendicitis, which affects roughly 7% of the world's population, is the leading cause of surgical acute abdomen worldwide. Because it is a more common condition in men, 8.6% of men will experience acute appendicitis at some point in their lives, compared to 6.7% of women. Objective: To gain a better understanding of this condition, which is so common in emergency care, we will study the clinical and epidemiological profile of patients undergoing appendectomy surgery in a reference hospital in Vitória - ES. Methods: The analysis of electronic medical records served as the foundation for this descriptive, retrospective investigation. The study will look at appendectomized patients in 2020 and examine their epidemiological profile, the length of their hospital stays, the type of operation they had, when they entered the emergency room, and any potential problems. Results: The majority of patients are male between the ages of 18 and 30 who are subjected to computed tomography for confirmation of the diagnosis. When appendicitis was confirmed, every patient underwent a laparoscopic appendectomy (51.62%). The most frequent complication, an intra-abdominal abscess, occurs at a rate of 17.2% and is usually caught early. Only 0.93 percent of patients died. Conclusion: The examination of the patient's profile will help us develop methods for making a quicker and more precise diagnosis, shortening the interval between care and definitive treatment, and decreasing hospital stays.
Keywords: Appendicitis; Acute abdomen